Disclosure of The Role of Intellectual Capital in Mediating Managerial Capability and Corporate Value - Lindawati Lindawati; Helmi Yazid; Ewing Yuvisa Ibrani (PT. EQUATOR SINAR AKADEMIA, 2023)
This study aims to examine the effect of managerial ability on intellectual capital disclosure, examine the effect of managerial ability on firm value, examine the effect of intellectual disclosure on firm value and examine the role of intellectual capital disclosure in mediating the relationship between managerial ability and firm value. This study uses secondary data derived from the financial statements of basic and chemical companies listed on the Indonesia Stock Exchange. By using the sampling technique purposive sampling method. Using a statistical application in the form of Structural Equation Modeling through the Wrap Partial Least Square application version 8.0 is used in this study to analyze research consisting of validity, reliability and hypothesis testing. The results of this study indicate that the first managerial ability has a positive effect on firm value, the second hypothesis shows managerial ability on intellectual capital disclosure, the third hypothesis shows intellectual capital disclosure on firm value, while the fourth hypothesis shows that intellectual capital disclosure mediates managerial ability on firm value. The conclusion of this study is managerial ability Managerial ability can be used to provide opportunities for managers who are involved in share ownership so that with this involvement the manager's position is equal to that of the shareholder.